Career Termination in Athletes: Identity Loss and Mental Health Strategies - Enoiu, Razvan Sandu; Aidar, Felipe (Health Nexus, 2025)
This study examines the psychological and physiological impacts of athletic career termination, focusing on identity loss and mental health trajectories among elite athletes. It evaluates the effectiveness of a multimodal intervention program designed to facilitate post-retirement adjustment through identity reconstruction and lifestyle adaptation strategies. A mixed-methods longitudinal design was employed with 138 retiring elite athletes (72 male, 66 female) across 28 sports disciplines. Participants were assessed at three timepoints (pre-retirement, 3-month, and 12-month post-retirement) using validated measures including the Athletic Identity Measurement Scale (AIMS-7), Depression Anxiety Stress Scales (DASS-21), and physiological markers (cortisol, heart rate variability). The intervention group (n=69) received 18 sessions combining cognitive-behavioral therapy, narrative identity exercises, and lifestyle redesign, while controls (n=69) received standard transition services. Qualitative interviews with 32 participants provided in-depth experiential data. Athletic identity showed a 32% mean reduction (d=1.2) with steepest decline at 3 months post-retirement. Mental health symptoms followed a U-shaped trajectory, peaking at 3 months (depression M=8.7; anxiety M=7.5) before improving. The intervention group demonstrated superior outcomes: 41% lower depression scores among physically active participants (p<0.001) and greater psychological integration (d=0.73). Physiological markers correlated with psychological distress (r=0.47), with faster cortisol normalization (-23% vs -14%) in the intervention group. Individual sport athletes showed 38% identity reduction versus 27% in team sports. Athletic retirement triggers significant identity disruption and mental health challenges, particularly during early transition. Structured interventions addressing identity continuity and lifestyle adaptation effectively mitigate these effects. Sports organizations should implement proactive transition programs combining psychological support with physiological monitoring.